SOILS NATURAL FERTILITY OF MADEIRA-RO FLUVIAL PLAIN: A PHYSIC-CHEMISTRY ANALYSIS (CEC, m% E V%) OF THE STRETCH FROM PORTO VELHO-RO TO HUMAITÁ-AM - Tatiane Rodrigues Lima; Dorisvalder Dias Nunes; Joiada Moreira da Silva; Déborah Pereira Linhares; Angelo Mansur Mendes; Danielle Freire Azevedo Silva (Sociedade & Natureza)
This work evaluates natural soil fertility on plain and flooded terrace areas, at Madeira River-RO fluvial plain, based on physics and chemicals analyses, (pH, OM, Al+2 + H+, exchange bases K+; Ca+2; Mg+2 e Al+3), physic-chemical (CEC, m% and V%), from the city of Porto Velho-RO to the city of Humaitá-AM. This kind of soil analysis is accomplished based on the percentage of base saturation (V%), which consists on physic-chemical phenomenon of ion absorption on clay and organic matter (OM) minerals. The soil samples were collected from temporary flooded plain strips and fluvial terraces with 20 km of intervals and 10 profiles described along the way, totalizing forty one (41) horizons. Using the EMBRAPA (1997) methods, the horizons A and B of each profile were considered. The results indicate four profiles with natural fertility deficiency: the Yellow Latosols at profile 1 and 2, Plintosols at profile 6 and Fluvic Neosols at profile 10, which may be related to the soil acidity, associated with high values of Al+3, as well on plain soils (Plintosols and Fluvic Neosols), as fluvial terrace (Latosols). Soils under the influence of flooding regime present high V%. The potential CEC values of analyzed horizons, were found low in consequence of the mineral composition of the clay, its values were correlated to the OM activities. However, the highest clay samples activities have been found on the superficial horizon of Plintosols at profile 6 (Cavalcante Community), where the potential CEC has arisen despite of reduction of OM content. The CEC varies from soil to soil, and what determine its values are the organic colloid/clay structures and the quantity of OM.